Strategies to Improve Entrepreneurial Behavior in Online Selling Through Advances in Entrepreneurial Characteristics, Intellectual Agility and Business Environment - Nusron, Anis; Setiawan, Margono; Noermijati, Noermijati; Rofiaty, Rofiaty (KnE Social Sciences, 2022)
This study aims to examine the effect of entrepreneurial characteristics, intellectual agility and business environment on entrepreneurial behaviours in selling online. This study used a quantitative approach. The population in this study were embroidery entrepreneurs in Pasuruan, East Java, who do business online. The sample used in this study was 180 respondents, and the sampling technique was purposive sampling. The data was obtained through a questionnaire. The results showed that entrepreneurship, intellectual agility and the business environment significantly affected entrepreneurial behaviour in selling online. The business environment weakens but does not significantly influence the effects of entrepreneurial characteristics and intellectual agility on entrepreneurial behaviour. Intellectual agility can partially mediate the influence of entrepreneurial characteristics in selling online. The implication of this research is, that for embroidery business actors, it is hoped that they will be able to carry out entrepreneurial behavior through maximizing their entrepreneurial characteristics and intellectual agility Keywords: entrepreneurial characteristics, intellectual agility, business environment, online entrepreneurial behaviour